[tex]\displaystyle \left\{ \frac{8}{35}+ \left[\left( \frac{3}{2} - \frac{33}{35} \right)+\left( \frac{3}{14} - \frac{2}{35} \right)-\left(2- \frac{12}{7} + \frac{5}{14} \right)\right]\right\} \cdot 3 \frac{1}{3} =\\ \\ =\left[ \frac{8}{35} + \left( \frac{105-66}{70} + \frac{15-4}{70} - \frac{28-24+5}{14} \right)\right] \cdot \frac{10}{3} =[/tex]
[tex]\displaystyle =\left[ \frac{8}{35} + \left( \frac{39}{70} + \frac{11}{70} - \frac{9}{14} \right)\right] \cdot \frac{10}{3}=\left( \frac{8}{35} + \frac{39+11-45}{70} \right) \cdot \frac{10}{3} = \\ \\ =\left( \frac{8}{35} + \frac{5}{70} \right) \cdot \frac{10}{3} = \frac{16+5}{70} \cdot \frac{10}{3} = \frac{21}{70} \cdot \frac{10}{3} =1[/tex]